Designing (for) Urban Food Webs - Felson, Alexander J.; Ellison, Aaron M. (Frontiers in Ecology and Evolution, 2021)
Interest is growing in designing resilient and ecologically rich urban environments that provide social and ecological benefits. Regenerative and biocentric designs fostering urban ecological habitats including food webs that provide ecosystem services for people and wildlife increasingly are being sought. However, the intentional design of urban landscapes for food webs remains in an early stage with few precedents and many challenges. In this paper, we explore the potential to design (for) urban food webs through collaborations between designers and ecologists. We start by examining the ecology and management of Jamaica Bay in New York City as a case study of an anthropogenic landscape where ecosystems are degraded and the integrity of extant food webs are intertwined with human agency. A subsequent design competition focusing on ecological design and management of this large-scale landscape for animal habitat and ecosystem services for people illustrates how designers approach this anthropogenic landscape. This case study reveals that both designing urban landscapes for food webs and directly designing and manipulating urban food webs are complicated and challenging to achieve and maintain, but they have the potential to increase ecological health of, and enhance ecosystem services in, urban environments. We identify opportunities to capitalize on species interactions across trophic structures and to introduce managed niches in biologically engineered urban systems. The design competition reveals an opportunity to approach urban landscapes and ecological systems creatively through a proactive design process that includes a carefully crafted collaborative approach to constructing ecologically functioning landscapes that can integrate societal demands. As designers increasingly seek to build, adapt, and manage urban environments effectively, it will be critical to resolve the contradictions and challenges associated with human needs, ecosystem dynamics, and interacting assemblages of species. Ecologists and designers are still discovering and experimenting with designing (for) urban food webs and fostering species interactions within them. We recommend generating prototypes of urban food webs through a learning-by-doing approach in urban development projects. Design and implementation of urban food webs also can lead to research opportunities involving monitoring and experiments that identify and solve challenges of food-web construction while supporting and encouraging ongoing management.